COMMONLY ISOLATED ORGANISM IN DIABETIC FOOT AND ITS ANTIBIOTIC SENSITIVITY, AN EXPERIENCE AT TERTIARY CARE HOSPITAL - Muhammad Iqbal Khan; Riffat Arbab.; Abdullah Khan; Maria Mehmood; Aisha Arshad; Hafsa Jaffar; Hafsa Qazi (Journal of University Medical & Dental College, 2020)
Abstract BACKGROUND & OBJECTIVE: To determine the commonly isolated organism in ulcers of diabetic foot and its sensitivity to antibiotics. METHODOLOGY: A total of 167 patients of diabetic foot were included in this descriptive Crosssectional study. All the patients were informed and consent was obtained according to ethical criteria approved by the ethical committee. The use of antibiotics in last 72 hours was strictly observed. The samples were obtained under aseptic conditions by applying the swap slightly to the exudate or base of the ulcer and were then carefully transferred in to the container and were then sent to the laboratory on the same date. The culture sensitivity was performed. Data was analyzed using SPSS. 20. RESULTS: A total of 140 samples were positive for 8 types of bacteria out of 167. 94 samples were monomicrobial were as 46 were polymicrobial. Over all Staphylococcus aureus 63(40.3%) was the most commonly isolated bacteria followed by Pseudomonas aeruginosa 40 (25.6%). S. aureus was most sensitive to imipenem/ meropenem (79.3%) followed by vancomycin (71%), linezolid (69.8%) and moxiﬂoxacin (69.8%). P. aeruginosa was sensitive to impenem/ meropeneum (90%) followed by Ticarcilline/ clavulante (92.5%), amikacin (87.5%) and pipracilline / tazobactom (80%). Most of the gram positive and negative bacteria were resistant to commonly available antibiotic like ampiciline/ cloxacillin, amoxicilline/ clavulante and cephradine. CONCLUSION: Most of the commonly used antibiotics had developed resistance. was S. aureus most common bacteria from the isolates and was sensitive to impenem/meropenem, vancomycin and linezolid. Gram-negative bacteria showed sensitivity to impenem/meropeneum, pipracilline/ tazobactom, Ticarcilline/ clavulante and amikacin.